NearTree, a data structure and a software toolkit for the nearest-neighbor problem - Andrews, Lawrence C (Journal of applied crystallography, 2016)
Many problems in crystallography and other fields can be treated as nearest-neighbor problems. The neartree data structure provides a flexible way to organize and retrieve metric data. In some cases, it can provide near-optimal performance. NearTree is a software tool that constructs neartrees and provides a number of different query tools